Crisis Management Handling, Corporate Reputation, and Customer Trust in Urban Public Transportation: Evidence from KAI Commuter Users among University Students in Jabodetabek - Annisa Fitriyani; Veranus Sidharta (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2026)
This study examines the influence of crisis management handling on corporate reputation and customer trust in urban public transportation, focusing on KAI Commuter users among university students in Jabodetabek. Public transportation disruptions, such as delays, overcrowding, operational failures, and unclear information, may erode passengers' confidence and damage an organization's reputation if not managed effectively. Using a quantitative explanatory survey design, data were collected from 150 university students who actively used KAI Commuter services and had experience or knowledge of service disruptions. The variables were measured using a five-point Likert-scale questionnaire and analyzed with simple linear regression. The findings indicate that crisis management handling has a positive and significant effect on corporate reputation, with a regression coefficient of 0.721 and an R² value of 0.556. Crisis management handling also positively and significantly affects customer trust, with a regression coefficient of 0.760 and an R² value of 0.521. These results suggest that rapid response, transparent information, empathy, appropriate solutions, and service improvement are essential in maintaining reputation and strengthening trust in commuter rail services. The study contributes to the literature on crisis communication, service recovery, and public transportation management in Indonesian metropolitan mobility.